Screening for frailty among older emergency department visitors: Validation of the new FRESH-screening instrument. Issue 1 (December 2016) - Kajsa, Eklund; Katarina, Wilhelmson; Sten, Landahl; Synneve, Ivanoff-Dahlin
Abstract Background The identification of frail older persons in different health care settings is widely seen as an important step in improving the healthcare system. Screening at an emergency department (ED) should be handled in just a few minutes without the use of tests or measurements. The FRESH-screening was developed for this purpose. This study's aim was to evaluate the FRESH-screening and its construct validity; also assessed were the sensitivity, specificity, and predictive values for frailty screening. Methods The study had a cross-sectional design. A total of 161 elderly people who sought care at the emergency department at Mölndal Hospital were included. Inclusion criteria were ages ≥80 years or ages 65–79 with at least one chronic disease and dependence in at least one daily living activity. Sensitivity, specificity, and predictive values were calculated to describe the accuracy of the FRESH-screening in identifying those with frailty, as assessed by eight frailty indicators. Sensitivity and specificity were both set at a minimum of 80 %, and a percentage sum ≥150 of the sensitivity and positive prediction was considered a measure of excellent value. Result Both sensitivity and specificity were high (81 % and 80 %, respectively) when comparing the four questions of the FRESH-screening against the eight frailty indicators. The percentage sum of sensitivity and positive prediction was 173 (81 % + 92 %), thus exceeding the 150 cutoff. Conclusion This study shows the FRESH-screening to be of excellent clinical value. Additionally, the clinical experience is that the instrument is simple and rapid to use, takes only a few minutes to administer, and requires minimal energy input by older persons.